Consumption of Risky Foods as a Risk Factor for Diabetes Mellitus in Indonesia - Basiroh, Umi Malikhatul; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
Background: Diabetes Mellitus (DM) is a non-communicable disease whose prevalence continues to increase in Indonesia and the world. Based on the 2023 Indonesian Health Survey (SKI) report, consumption of risky foods such as sweet foods and drinks, fatty/fried foods, salty foods, processed foods, and soft drinks is still high in various community groups. Several studies have shown that consumption of foods high in sugar and fat is closely related to an increase in the incidence of DM. Therefore, an in-depth analysis is needed regarding the pattern of consumption of risky foods as the main factor in the development of DM in Indonesia. Objective: This study aims to analyze the relationship between consumption of risky foods and the incidence of DM in Indonesia based on data from SKI 2023. Method: The method used in this study is quantitative descriptive analysis based on secondary data from SKI 2023 and several related scientific articles. The analysis was conducted using a cross-sectional approach to see the consumption patterns of risky foods in various community groups, and analyzed univariately to determine the consumption of risky foods with the incidence of DM. Results: Consumption of risky foods in Indonesia is still high, especially among children, adolescents, and people with low levels of education. As many as 47.5% of the population consumes sweet drinks every day, while fatty and fried foods are consumed by 37.4% of the population every day. Consumption of risky foods is more common in young age groups, who are at high risk of obesity and prediabetes. In addition, people with low education tend to consume more processed foods and fatty foods than those with higher education. Various interventions are needed to reduce the risk of DM due to unhealthy food consumption patterns.